Increased carotid intima–media thickness is not associated with T-cell activation nor with cytomegalovirus in HIV-infected never-smoker patients. (28th January 2015) - Goulenok, Tiphaine; Boyd, Anders; Larsen, Martin; Fastenackels, Solène; Boccara, Franck; Meynard, Jean-Luc; Hadour, Nabila; Samri, Assia; Desvarieux, Moïse; Autran, Brigitte; Appay, Victor; Girard, Pierre-Marie; et al.
<x xml:space="preserve">Abstract</x> Objectives: Increased risk of cardiovascular disease in patients infected with HIV has been attributed to immune activation, inflammation, and immunosenescence, all of which are linked to chronic immune activation by viral infections, particularly cytomegalovirus (CMV). Our aim is to evaluate the impact of these atherogenic markers in HIV-infected patients who never smoked. Design: Exposure-matched, cross-sectional study. Methods: In 59 HIV-infected individuals [n = 30 undergoing ≥4 years of antiretroviral therapy (ART); n = 29 never treated with ART] and 30 age-matched HIV-negative controls, we measured the level of activation and senescence, as well as the frequency of CMV-specific T cells, on peripheral blood mononuclear cells, while examining their association with carotid intima–media thickness. Partial correlations were adjusted for age, systolic blood pressure, and nadir CD4+ cell count. Results: The previously described roles of T-cell activation, CMV, and immunosenescence in the atherosclerotic risk of HIV-infected patients, as assessed by carotid intima–media thickness, were not apparent in our cohort of particularly 'healthy' HIV-infected never-smokers. Conclusion: In HIV-infected individuals at low cardiovascular disease risk, our data show that the increased risk of carotid atherosclerosis is not associated with immunological markers described to be associated with HIV disease progression.